2021
DOI: 10.7554/elife.61173
|View full text |Cite
|
Sign up to set email alerts
|

The role of P2Y12 in the kinetics of microglial self-renewal and maturation in the adult visual cortex in vivo

Abstract: Microglia are the brain's resident immune cells with a tremendous capacity to autonomously self-renew. Because microglial self-renewal has largely been studied using static tools, its mechanisms and kinetics are not well understood. Using chronic in vivo two-photon imaging in awake mice, we confirm that cortical microglia show limited turnover and migration under basal conditions. Following depletion, however, microglial repopulation is remarkably rapid and is sustained by the dynamic division of remaining mic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 55 publications
3
22
0
Order By: Relevance
“…During depletion, surviving microglia are seen scattered throughout the brain (Figure 1A-B, C) and subsequent withdrawal of the inhibitor results in rapid and spatially homogenous microglial repopulation within 3d, with cells exceeding control numbers by 7d (Figure 1C, E). Recent studies show that repopulation is dependent on the local proliferation and clonal expansion of surviving microglia 24,26,27,[31][32][33] ; thus, we refer to this type of repopulation as global microglial (GLOBAL) repopulation.…”
Section: Cns Repopulationmentioning
confidence: 99%
“…During depletion, surviving microglia are seen scattered throughout the brain (Figure 1A-B, C) and subsequent withdrawal of the inhibitor results in rapid and spatially homogenous microglial repopulation within 3d, with cells exceeding control numbers by 7d (Figure 1C, E). Recent studies show that repopulation is dependent on the local proliferation and clonal expansion of surviving microglia 24,26,27,[31][32][33] ; thus, we refer to this type of repopulation as global microglial (GLOBAL) repopulation.…”
Section: Cns Repopulationmentioning
confidence: 99%
“…In this present study, we investigated the impact of pharmacologically induced microglial renewal on pathology, microglial activation, and gene expression using both the 3xTg and APP/PS1 mouse models of Alzheimer’s disease. Previous work from our laboratory and others demonstrated that adult microglia are capable of rapid self-renewal following depletion [ 28 , 47 ]. These new-born microglia are thought to be “rejuvenated” and beneficial in the context of disease settings such as toxin-induced acute neuronal lesion as well as normal aging [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adult microglia have a remarkable capacity to selfrenew, and after depletion, repopulate their niche completely within 1 week, acquiring their normal densities, spacing, and morphological characteristics [25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%
“…It would be of great interest to determine specific markers which allow the precise identification of highly neurotoxic and/or degenerated plaque-associated microglia, in order to specifically deplete them. Microglial proliferation which repopulate the depleted niche rapidly acquire mature characteristics [ 58 , 101 ] and may counteract AD pathology by better containing amyloid deposits and diminishing pathological phagocytosis of synapses, then contributing to the amelioration of AD cognitive decline.…”
Section: Do Microglia Refresh or Poison Ad Progression?mentioning
confidence: 99%